2021
DOI: 10.1126/science.abf1730
|View full text |Cite
|
Sign up to set email alerts
|

The G protein signaling regulator RGS3 enhances the GTPase activity of KRAS

Abstract: Paving the way for KRAS inhibitors KRAS is a key oncogene in multiple cancer types, but existing inhibitors target only a mutant form of KRAS containing the G12C mutation, and their function presents a mechanistic conundrum. It is known that KRAS G12C inhibitors bind to the oncoprotein in its inactive form; however, KRAS mutations such as G12C interfere with the action of proteins that normally help it hydrolyze GTP to achieve the inactive state. Li et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…In addition to SOS-catalysed nucleotide exchange, GAP-stimulated GTP hydrolysis was also analysed. While the intrinsic GTP hydrolysis of KRasG13C-edaGTP (t 1/2 = 187 min) is comparable to that of KRasWT:GTP (t 1/2 = 126 min) and even faster than for the KRasG12C mutant (t 1/2 = 300 min) 25 (Figure S15), a drastically decreased GAP-stimulated GTP hydrolysis was observed for the G13C mutant as expected. 26 After a detailed in vitro characterization of the nucleotide analogues, the next experiment was to investigate whether oncogenic signalling could also be inhibited in vivo.…”
Section: Inhibition Of Oncogenic Krasg13c Signalling By Covalent Nucl...supporting
confidence: 72%
See 1 more Smart Citation
“…In addition to SOS-catalysed nucleotide exchange, GAP-stimulated GTP hydrolysis was also analysed. While the intrinsic GTP hydrolysis of KRasG13C-edaGTP (t 1/2 = 187 min) is comparable to that of KRasWT:GTP (t 1/2 = 126 min) and even faster than for the KRasG12C mutant (t 1/2 = 300 min) 25 (Figure S15), a drastically decreased GAP-stimulated GTP hydrolysis was observed for the G13C mutant as expected. 26 After a detailed in vitro characterization of the nucleotide analogues, the next experiment was to investigate whether oncogenic signalling could also be inhibited in vivo.…”
Section: Inhibition Of Oncogenic Krasg13c Signalling By Covalent Nucl...supporting
confidence: 72%
“…The copyright holder for this preprint this version posted July 25, 2022. ; https://doi.org/10.1101/2022.07. 25.501348 doi: bioRxiv preprint 3 nucleotide competitive inhibitors that can covalently bind to KRasG12C. 18,19 Strategies involving direct competition with nucleotide binding were originally set aside because of the high affinity of GDP/GTP for Ras and high cellular GDP/GTP concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The rate at which this happens is limited by the slow conversion of mutant KRAS G12C -GTP to KRAS G12C -GDP, to which the drug binds, although other factors may impact this in vivo. For example, Li et al 20 recently showed that, in some cancer cells, the proportion of KRAS G12C in the inactive form may be higher than expected because other cellular enzymes of the regulator of G proteins family happen to convert the active form of KRAS G12C -GTP to the GDP form by an off-target GTPase-activating protein mechanism.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…A remaining barrier is the genotype specificity of current clinically available inhibitors, as G12C mutations account for nearly half (46%) of mutations in NSCLC [ 7 ] but only 4–14% of KRAS mutations in all human cancers [ 33 ]. One of the unique features of the KRAS G12C mutant is its retention of near wild type intrinsic GTPase activity, allowing covalent inhibitors to selectively target the inactive GDP state and retain high efficacy [ 34 ]. In contrast, the KRAS G12D mutant demonstrates a high nucleotide exchange rate.…”
Section: Strategies To Target Oncogenic Mutant Krasmentioning
confidence: 99%